Synthesis and Spectroscopic Characterizations of Ni(II) Thiosemicarbazone Bearing Anthracene - Hien, Dinh Thi; Ha, Khuat Thi Thuy; Dat, Nguyen Tien; Thao, Dinh Thi; Hai, Nguyen Minh (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 2, 2021)
The X-ray structure of 9-anthraldehyde-4-methyl-3-thiosemicarbazone was firstly determined.  The Ni(II) complex with this ligand was prepared upon reaction with chloride salt. Mass spectrometry result confirms correct formulation of the complex. Unusual 1 H NMR signal pattern of anthracene moiety reveal cis arrangement cemented by intramolecular p–p stackings between aromatic rings. As a result of this interaction, the electronic structure of anthracene ring is perturbed and gives rise to structureless and broad absorption and emission bands.